Struktur Komunitas Moluska: Gastropoda dan Bivalvia di Vegetasi Perairan Danau Sentani Papua - Suriani Br Surbakti; Leonardo A. Numberi; Roma M. Manalu (Jurnal Biologi Papua, 2022)
Community structure of bivalvia and gastropods nearby water vegetation in Sentani Lake, Papua. Line’s transect and plot methods were used to determining the structure of mollusks and vegetation by using index, diversity, and dominance as parameters. Intentional measurement were carried out on several biological parameters of the waters at 10 sampling points. From the observation and measurments, we obtained seven types of mollusk with 5644 individuals, where six types are belong to gastropods and one type is a member of bivalves. The highest level of mollusk diversity was in Kwadeware, the highest at the inlet of the lake, and were dominated by Melanoides tuberculata and Pomacea canaliculata. In addition, vegetation found in the area observation were water hyacinth (Eichhornia crassipes), water spinach (Ipomoea aquatica), apu wood (Pistia stratiotes), genjer (Limnocharis flava), Hydrilla verticillata, seagrass (Potomogeton malainus), Nymphaea alba, Ceratophyllum demersum, and Nymphoides indica.Key words: gastropods; molluscs; vegetation; Sentani lake